Lipase-catalyzed synthesis of acid-degradable poly(β-thioether ester) and poly(β-thioether ester-co-lactone) copolymers. (24th February 2015) - Wu, Wan-Xia; Qu, Lin; Liu, Bei-Yu; Zhang, Wei-Wei; Wang, Na; Yu, Xiao-Qi
Abstract: A novel linear polyester with acid-labile β -thiopropionate groups was synthesized via the direct lipase-catalyzed polycondensation of methyl 3-((2-hydroxyethyl)thio)propanoate (MHETP) using immobilized lipase B from Candida antarctica (CALB). The influences of reaction conditions such as polymerization temperature and time on the molecular weight of the poly( β -thioether ester) (PTE) were studied. Ring-opening and condensation copolymerization of MHETP with ε -caprolactone (CL) led to the synthesis of novel poly( β -thioether ester- co - ε -caprolactone) copolymers, poly(TE- co -CL), with well-defined composition and narrow polydispersity. The random copolymers were characterized by 1 H NMR, 13 C NMR, 2D NMR, GPC, TGA and DSC. The degradation of the poly( β -thioether ester) under acidic conditions was investigated by GPC and 1 H NMR spectroscopy. Graphical abstract: Highlights: Lipase-catalyzed polycondensation synthesis of acid-degradable poly( β -thioether ester). Novel poly( β -thioether ester- co - ε -caprolactone) copolymers with high molecular weights were obtained. Poly( β -thioether ester) could rapidly degrade by the hydrolysis of the β -thiopropionate groups under acidic condition.